Interference effects between duct and control vane on a micro air vehicle / Sheila Tobing, Tiauw Hiong Go and Roxana Vasilescu - Hiong Go, Tiauw; Vasilescu, Roxana (Faculty of Mechanical Engineering and University Publication Centre (UPENA), 2009)
A numerical study on the interference effects between duct and control vanes on a Vertical Takeoff and Landing Micro Air Vehicle is presented in this paper. The numerical analysis is conducted systematically with the solver first validated before it is applied to the full vehicle simulations. Different combinations of duct and control vanes are tested to determine the interactions between the two components and their effects on the vehicle's aerodynamics. The simulations show that the duct influences the local flow around the control vanes. The duct redirects the flow before it passes the control vanes, altering the aerodynamic forces and moment generated by the vanes as well as the vehicle. The control vanes generate lower aerodynamic forces and moments under the influences of the duct, compared to when they are simulated as isolated (individual) components. The over-predictions of the vehicle's aerodynamic forces and moments need to be taken into consideration in designing as they will introduce a high error to the design.